Implementation of a Contingency Management-Based Intervention in a Community Supervision Setting: Clinical Issues and Recommendations - TROTMAN, ADRIA J. (2011)
A cognitive-behaviorally based substance abuse treatment program was implemented within a Community Supervision setting. This program included a goals group that included a contingency management component and included the probation agent as a part of treatment. This paper describes the contingency management component of the treatment and discusses, in detail, issues that arose throughout the course of the study. Possible causes and solutions to the issues are discussed from a contingency management perspective that can result in improved reinforcements to achieve better probationer outcomes.